1978
DOI: 10.1093/ajcn/31.10.1956
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid content of erythrocytes in uremia

Abstract: The amino acid content of plasma and erythrocytes in patients with severe renal failure (serum creatinine less than 8 mg/100 ml) treated with selective low-protein diets, in patients on regular hemodialysis, and in a control group of healthy subjects were studied. Most amino acids in erythrocytes of the patients showed the same changes as in plasma with the exception of histidine, serine, and alanine. In spite of low histidine plasma levels, the erythrocytes level is increased as compared with healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Hemodialysis led to a decrease in plasma phenylalanine level without influencing its concentra tion in erythrocytes. Similar observations concerned with the behavior of several other amino acids were reported by Jontofsohn et al [8], They suppose that red blood cells can rapidly replenish their free amino acid content by a direct amino acid uptake from tissues. This explanation is consistent with the experimental data reported by £/-wyn et al [5,6] who found that the amino acid transport across the cell membrane of dog erythrocytes took place during the passage of erythrocytes through the hepatic capillary bed, lasting only a few seconds.…”
Section: Discussionsupporting
confidence: 81%
“…Hemodialysis led to a decrease in plasma phenylalanine level without influencing its concentra tion in erythrocytes. Similar observations concerned with the behavior of several other amino acids were reported by Jontofsohn et al [8], They suppose that red blood cells can rapidly replenish their free amino acid content by a direct amino acid uptake from tissues. This explanation is consistent with the experimental data reported by £/-wyn et al [5,6] who found that the amino acid transport across the cell membrane of dog erythrocytes took place during the passage of erythrocytes through the hepatic capillary bed, lasting only a few seconds.…”
Section: Discussionsupporting
confidence: 81%
“…The sulphosalicylic acid extracts were stored at -7 0°C . Amino acids were analyzed by means o f a conventional single-col umn ion-cxchangc method with a lithium buffer system [25].…”
Section: Mel Hodsmentioning
confidence: 99%
“…In contrast to what was reported, no change in valine and leucine levels was found. Serine and glycine increased slightly and transiently: however, these changes can be accounted for by an increase in the red cell mass, since red blood cells contain higher concentrations of these AA [15]. Interestingly, aspartate, which is mainly contained in the blood cell compartment, did not increase despite the augment in the red blood cell mass.…”
Section: Discussionmentioning
confidence: 86%